Krishna
0

Step 1: Recall The Law of Cosines


triangle angles A,B,C and sides a,b,c

ab and c are sides.

C is the angle opposite side c

The Law of Cosines (also called the Cosine Rule) says:

c^2 = a^2 + b^2 - 2ab cos (C)


Step 2: Look at the figure and note down the given values.


Step 3: Substitute the known values in the Cosine rule.

            EXAMPLE: c^2 = a^2 + b^2 - 2ab cos (C)

                               z^2 = (9.4)^2 + (6.5)^2 - 2(9.4)(6.5) cos (131)


Step 4: Do some calculations

                               z^2 = 88.36 + 42.25 - 122.2 * (-0.656)

                               z^2 = 130.61 + 80.17


Step 5: Apply the square root on both sides. To know the unknown length.

                               z^2 =210.78

                               z = \sqrt{210.78}

                                        z = 14.5